Synthesis Thin Films SnO2 with Doping Indium by Sol-gel Spin coating - Syamsul Hakim; Aris Doyan; Susilawati Susilawati; Lalu Muliyadi (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract:This research is an experimental study that aims to support the temperature and variation of doping in making thin films. The temperature variations at room temperature annealing, 50, 100, 150, and 200oC, and doping variations of 0, 5, 10, 15, 20, and 25%. The method used in this study is sol-gel spin coating. The results showed that thin films at low temperatures were more transparent than higher temperatures and the increase percentage doping causing thin films to be more transparent. Keywords:Thin Films; SnO2; Indium, Sol-gel, Spin Coating.